MicroRNA-1 and Circulating Microvesicles Mediate the Protective Effects of Dantonic in Acute Myocardial Infarction Rat Models - Sun, Tingting; Zhang, Lihua; Li, Xinxin; Chen, Fengfei; Li, Yanchuan; Ma, Xiaohui; Yu, Feng (Frontiers in Physiology, 2018)
Aim: To investigate the protective effect of dantonic in ischemic myocardial damage by evaluating the expression of circulating microvesicles (MVs) and microRNA-1 (miR-1) in two animal models. Methods: Two animal models of myocardial ischemia were established that were isoproterenol-induced myocardial ischemia (ISO-AMI) rat model and the acute myocardial infarction rat model induced by ligation of the left anterior descending coronary artery (LAD-AMI) of rat. To investigate the protective effect of dantonic, we observed the myocardial infarction size, creatine kinase (CK), lactate dehydrogenase (LDH), aspartate aminotransferase (AST) activities, cardiac troponin I (cTnI) level in serum, and the plasma levels of miR-1 and MVs. Results: The results showed that pretreatment with dantonic significantly attenuated the LAD-AMI induced myocardial damage by decreasing the size of myocardial infarction, CK, LDH, AST activities, and cTnI level in serum. High dose dantonic treatment could significantly abrogate the increased plasma levels of miR-1 and MVs as compared to the LAD rat model. In addition, pretreatment with dantonic also showed a significant myocardial protective effect through reducing the expression levels of CK, LDH, and AST as compared to the ISO-AMI model. Whereas the cTnI level was no significant difference between model group and control group, suggesting that the model caused less myocardial damage. In the ISO-induced myocardial ischemia model, there is no significant difference between the model group with the control group of MVs and miR-1 levels. This may be that miR-1 is reported as a biomarker of acute myocardial infarction. The pathological changes of IOS-induced acute myocardial ischemia model are also different from those of acute myocardial infarction. Conclusion: Dantonic showed the protective effect in these two ischemic myocardial injury rat models, whereas the circulating miR-1 and MVs levels were only ameliorated in the LAD rat model.